Ultra-low carbon clinker-free cement, its manufacturing method and use
By controlling the content of calcium oxide and calcium hydroxide in cement raw materials and using appropriate amounts of calcium oxide-based materials, the granulated slag of steel furnaces is activated, and the contradiction between cement reduction and strength development is solved, and the cement performance of high-strength and low-carbon emissions is achieved.
Patent Information
- Application Number
- JP2023527292
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2022-09-16
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2042-09-16
AI Technical Summary
The prior art is difficult to maintain the strength development of cement while reducing carbon emissions, and improper use of traditional activators leads to problems such as low early strength, reduced later strength, and easy corrosion.
Ultra-low-carbon clinker-free cement is used to control the content of calcium oxide and calcium hydroxide in the cement raw materials between 0.05% and 0.75%, and calcium oxide-based materials rich in free calcium oxide, such as limestone and quicklime, are used as activators to activate the granulated slag of the steel furnace to form high-strength calcium sulfa aluminate hydrate.
The cement properties of high initial strength, extremely high late strength, low shrinkage, low carbon emissions and carbonization resistance are achieved, avoiding the weaknesses brought by traditional activators.
Smart Images

Figure 0007628730000035 
Figure 0007628730000001 
Figure 0007628730000002
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of building materials, and in particular to an ultra-low carbon clinker-free cement and a method for producing the same. [Background technology]
[0002] Cement is an essential building material for modern society, meeting huge demands for infrastructure construction, but its production comes with high carbon emissions. 。
[0003] Super sulfate cement is a new low-carbon cement, usually made of granulated blast furnace slag as the main raw material, gypsum as the sulfate activator, and silicate clinker or lime as the alkaline activator. Super sulfate cement has excellent performance characteristics such as low heat of hydration, strong impermeability, and resistance to sulfate erosion, and has a simple manufacturing process, low cost, and low energy consumption. From the 1940s to the 1960s, super sulfate cement was widely used in the United Kingdom, Germany, France, Italy, Belgium, the Netherlands, and Luxembourg. However, since the 1970s, with the development of steelmaking technology, the chemical composition of granulated blast furnace slag has changed, which has reduced the reactivity of granulated blast furnace slag, and with the original material composition and manufacturing process, it is difficult to produce a gel material whose technical performance meets the requirements of the process. 。
[0004] The present invention has been made in view of the above circumstances. Summary of the Invention
[0005] The first object of the present invention is to provide an ultra-low carbon clinker-free cement to resolve the conflict between carbon dioxide emissions and strength development that exists in the cement sector.
[0006] A second object of the present invention is to provide a method for producing ultra-low carbon clinker-free cement, which has the advantages of being a simple process and suitable for industrial production.
[0007] In order to achieve the above object of the present invention, the following technical means are adopted. In a first aspect, the present invention provides an ultra-low carbon clinker-free cement produced from granulated blast furnace slag, gypsum, and calcium oxide-based raw materials, in which the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.75%, preferably the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.1% to 0.5%, and most preferably 0.16% to 0.5%.
[0008] In a preferred embodiment, the granulated blast furnace slag is 65% to 95% of the total raw material weight, and the gypsum is 4.5% to 34.5% of the total raw material weight; more preferably, the granulated blast furnace slag is 68% to 92% of the total raw material weight, and the gypsum is 7.5% to 31.5% of the total raw material weight; even more preferably, the granulated blast furnace slag is 70% to 90% of the total raw material weight, and the gypsum is 9.5% to 29.5% of the total raw material weight; and even more preferably, the granulated blast furnace slag is 70% to 90% of the total raw material weight, and the gypsum is 9.8% to 25% of the total raw material weight.
[0009] Based on the same idea, the present invention further provides an ultra-low carbon clinker-free cement produced from granulated blast furnace slag, gypsum, a cement admixture, and a calcium oxide-based raw material, in which the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.75%, preferably the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.5%.
[0010] In a preferred embodiment, the granulated blast furnace slag is 33% to 94% of the total weight of the raw materials, the gypsum is 4.5% to 34.5% of the total weight of the raw materials, and the cement admixture is 0.65% to 32% of the total weight of the raw materials; preferably, the granulated blast furnace slag is 35% to 90% of the total weight of the raw materials, the gypsum is 9.5% to 29.5% of the total weight of the raw materials, and the cement admixture is 0.65% to 25% of the total weight of the raw materials. More preferably, the granulated blast furnace slag accounts for 47% to 80% of the total raw material weight, the gypsum accounts for 19.5 to 20% of the total raw material weight, and the cement admixture accounts for 0.65% to 5% of the total raw material weight, and even more preferably, the granulated blast furnace slag accounts for 54% to 80% of the total raw material weight, the gypsum accounts for 9.8% to 19.5% of the total raw material weight, and the cement admixture accounts for 10% to 20% of the total raw material weight.
[0011] Based on the same idea, the present invention further provides an ultra-low carbon clinker-free cement produced from granulated blast furnace slag, gypsum, a setting control / strength enhancing component and a calcium oxide-based raw material, in which the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.75%, preferably the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.3%, and most preferably 0.16% to 0.2%.
[0012] In a preferred embodiment, the granulated blast furnace slag accounts for 63% to 94% of the total raw material weight, the gypsum accounts for 4.5% to 34.5% of the total raw material weight, and the set adjuster / strength enhancer components account for 0.9% to 1.95% of the total raw material weight; preferably, the granulated blast furnace slag accounts for 65% to 90% of the total raw material weight, the gypsum accounts for 9.5% to 29.5% of the total raw material weight, and the set adjuster / strength enhancer components account for 1% to 1.5% of the total raw material weight; and more preferably, the granulated blast furnace slag accounts for 77.5% to 79% of the total raw material weight, the gypsum accounts for 9.8% to 19.5% of the total raw material weight, and the set adjuster / strength enhancer components account for 1% to 1.2% of the total raw material weight.
[0013] Based on the same idea, the present invention further provides an ultra-low carbon clinker-free cement produced from granulated blast furnace slag, gypsum, a cement admixture, a setting control / strength enhancing component, and a calcium oxide-based raw material, in which the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.75%, preferably the weight percentage of calcium oxide and / or calcium hydroxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.2%.
[0014] In a preferred embodiment, the granulated blast furnace slag is 31% to 93% of the total weight of the raw materials, the gypsum is 4.5% to 34.5% of the total weight of the raw materials, the cement admixture is 0.65% to 32% of the total weight of the raw materials, and the setting regulator and strength enhancer is 0.9% to 1.95% of the total weight of the raw materials. Preferably, the granulated blast furnace slag is 35% to 85% of the total weight of the raw materials, and the gypsum is 9.5% to 29.5% of the total weight of the raw materials. %, the cement admixture is 1% to 20% of the total raw material weight, the set adjuster / strength enhancer is 1% to 1.5% of the total raw material weight, and more preferably, the granulated blast furnace slag is 50% to 80% of the total raw material weight, the gypsum is 9.8% to 19.5% of the total raw material weight, the cement admixture is 1% to 15% of the total raw material weight, and the set adjuster / strength enhancer is 1% to 1.2% of the total raw material weight.
[0015] In the ultra-low carbon clinker-free cement provided by the present invention, the calcium oxide-based material is a material that contains free calcium oxide as a main component and has a free calcium oxide content of 30% to 80%. The free calcium oxide is a general term for components that are present in the raw materials in the form of free calcium oxide and / or calcium hydroxide that are not bound to acidic oxides. The content of free calcium oxide can be measured by the test method specified in the national standard GB / T 176-2017. The description "controlling the weight percentage of calcium oxide and / or calcium hydroxide in the total weight of the cement raw materials" in the present invention means controlling the weight percentage of free calcium oxide relative to the total weight of the cement raw materials. Therefore, the "free calcium oxide" described below is a general term for components that are present in the cement raw materials in the form of free calcium oxide and / or calcium hydroxide. In the ultra-low carbon clinker-free cement of the present invention, the calcium oxide-based material is preferably any one or a combination of two or more of quicklime, slaked lime, industrial calcium oxide, industrial calcium hydroxide, carbide slag, a calcium oxide-based expanding agent, and an ettringite-based expanding agent. More preferably, the calcium oxide-based material is any one or a combination of two or more of quicklime, slaked lime, and carbide slag.
[0016] In the ultra-low carbon clinker-free cement provided by the present invention, the gypsum is any one or a combination of two or more of natural gypsum dihydrate, natural anhydrite, hemihydrate, α-type high-strength gypsum, desulfurized gypsum, phosphate gypsum, and hydrofluoric gypsum, and preferably, the gypsum is any one or a combination of two or more of natural gypsum dihydrate, natural anhydrite, hemihydrate, and desulfurized gypsum.
[0017] In the above embodiment of the present invention, the cement admixture is any one or a combination of two or more of fly ash, steel slag, limestone, dolomite, pozzolanic admixture or sandstone. The introduction of the cement admixture can further reduce the carbon dioxide footprint of the cement described in the present invention.
[0018] In the above embodiment of the present invention, the setting adjustment / strength enhancement component is any one or a combination of two or more selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium sulfate, sodium sulfate, potassium sulfate, aluminum sulfate, lithium carbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium silicate, lithium chloride, citric acid, sodium citrate, or sodium gluconate, and preferably, the setting adjustment / strength enhancement component is any one or a combination of two or more selected from lithium hydroxide, sodium hydroxide, lithium sulfate, sodium sulfate, aluminum sulfate, lithium carbonate, citric acid, sodium citrate, or sodium gluconate.
[0019] In a second aspect, the present invention provides a method for producing the ultra-low carbon clinker-free cement. The specific steps are as follows: after mixing all the raw materials, the mixture is mixed with a specific surface area of 300 to 700 m 2 / kg, controlling the weight percentage of free calcium oxide in the raw materials to 0.05% to 0.75%, preferably 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.2%, to obtain ultra-low carbon clinker-free cement.
[0020] In a preferred method for producing the ultra-low carbon clinker-free cement of the present invention, 1% to 50% by weight of the granulated blast furnace slag may be replaced with a cement admixture before being ground together with other raw materials, and then the ultra-low carbon clinker-free cement may be obtained.
[0021] In a preferred method for producing the ultra-low carbon clinker-free cement of the present invention, 0.1% to 3% by weight of the granulated blast furnace slag may be replaced with a setting regulator / strength enhancer component before being ground together with other raw materials, and then the ultra-low carbon clinker-free cement may be obtained.
[0022] In a preferred method for producing the ultra-low carbon clinker-free cement of the present invention, the granulated blast furnace slag may be replaced by a cement admixture and a setting regulator / strength enhancer by weight percentage before being ground together with other raw materials, and then ground together with other raw materials to obtain the ultra-low carbon clinker-free cement, where 1% to 50% of the granulated blast furnace slag is replaced by the cement admixture, and 0.1% to 3% of the granulated blast furnace slag is replaced by the setting regulator / strength enhancer.
[0023] In a preferred embodiment of the method for producing the present invention, the specific steps are: after all the raw materials are mixed, the specific surface area of the raw materials is 300-700 m 2 / kg, controlling the weight percentage of free calcium oxide in the raw materials to 0.05% to 0.75%, preferably 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.2%, to obtain ultra-low carbon clinker-free cement.
[0024] In another preferred embodiment of the production method of the present invention, the specific steps include: 2 / kg, and then crushed together with all other ingredients until the specific surface area is 300-700m 2 / kg, and then adding and mixing the crushed granulated blast furnace slag to control the weight percentage of free calcium oxide in the raw material to 0.05% to 0.75%, preferably to 0.05% to 0.7%, more preferably to 0.05% to 0.6%, more preferably to 0.05% to 0.5%, even more preferably to 0.10% to 0.5%, and most preferably to 0.16% to 0.2%, to obtain ultra-low carbon clinker-free cement.
[0025] In a third aspect, the present invention further provides the use of the ultra-low carbon clinker-free cement in the manufacture of concrete, mortar or cement products, in which the ultra-low carbon clinker-free cement of the present invention can be mixed and stirred together with a plurality of raw materials, such as mineral admixtures, aggregates, fibers, additives and water, to produce concrete, mortar or cement products.
[0026] In the prior art, it is usually necessary to add alkaline activators such as Portland cement, Portland cement clinker, and calcium oxide to activate granulated blast furnace slag. Existing research has shown that too little cement clinker will not achieve sufficient activation effect, and too much cement clinker will inhibit the hydration of granulated blast furnace slag. In fact, Portland cement, Portland cement clinker, calcium oxide, etc. are activator raw materials with relatively complex components, and their main components and action mechanisms have not yet been fully understood, so it is difficult to determine the appropriate amount of the above alkaline activator. If the amount used is too small, the activity of granulated blast furnace slag cannot be effectively activated, and the produced cement has a slow hardening rate, low early strength and late strength, and the slow hardening rate may cause the cement to be carbonated and corroded. If the amount used is too large, the early strength will be greatly improved, but the late strength will be greatly reduced, and the process requirements cannot be met. The inventors have found through experiments that a calcium oxide-based material mainly composed of an appropriate amount of free calcium oxide and / or calcium hydroxide, such as quicklime, can effectively activate granulated blast furnace slag and produce cement with excellent performance. First, free calcium oxide and / or calcium hydroxide, which are the main components of calcium oxide-based materials such as quicklime, react quickly when they come into contact with water, producing a large amount of OH. - It promotes the hydration of granulated blast furnace slag by releasing [Al(OH)4] - At the same time, when quicklime comes into contact with water, it produces another substance, Ca 2+ and releases [Al(OH)4] - and SO4 released by gypsum 2- It reacts with [Al(OH)4] to form ettringite, and the remaining [Al(OH)4] -produces aluminum gel. Ettringite is a fibrous crystal, has relatively high strength, and can fill voids, while aluminum gel is a colloid that has a gelling action and bonds ettringite crystals to each other to form a dense hardened body, which can give cement high early strength and later strength. The inventors have also found that the improvement in strength due to the activation of calcium oxide-based materials such as quicklime is already approaching its limit at low blending amounts (the weight percentage of free calcium oxide and / or calcium hydroxide blended with various calcium oxide-based raw materials is 0.05% to 0.75%), which is the optimal blending amount range. This blending amount range can be achieved by adding an appropriate amount of OH. - It can effectively activate granulated blast furnace slag by providing an appropriate amount of Ca 2+ However, the addition of more calcium oxide-based materials such as quicklime generates excess Ca(OH)2, which reacts with the aluminum gel and ettringite to generate calcium monosulfoaluminate hydrate, which has low strength, is easily carbonated, and has no corrosion resistance. This reaction causes the volume of the product to decrease, the hardened body to become loose, and the porosity to increase. This reaction also consumes the aluminum gel that has a gelling effect, making the amount of colloid in the system insufficient to bond other materials, significantly reducing the strength of the cement, and the calcium monosulfoaluminate hydrate that is easily carbonated, making the cement susceptible to corrosion due to carbonation. In addition, calcium oxide-based materials such as quicklime increase the hydration reaction rate in the system and the Ca 2+ and OH -The release rate of calcium oxide and / or calcium hydroxide in such materials is appropriate, and the activity of calcium oxide and / or calcium hydroxide in such materials is high and the reaction rate is fast when contacted with water, which is favorable for activating granulated blast furnace slag as quickly as possible, so that the cement has relatively high strength at an early stage and avoids carbonation and corrosion caused by the cement hardening too slowly. In fact, in terms of the effect on cement strength, the reaction rate is more important than the amount of calcium oxide-based material added. In the prior art, the added Portland cement or Portland cement clinker-based alkaline activator is mainly composed of tricalcium silicate and dicalcium silicate, and contains Ca 2+ and OH - However, the reaction rate is too slow, and it usually takes 1-7 days to generate sufficient effective activating components, which results in low early strength of cement, slow hardening rate, and severe carbonation corrosion. To improve the hardening rate and early strength of cement, the amount of alkaline activator is usually increased. However, these substances release excess Ca at a later stage, which is a problem. 2+ and OH - However, this can cause a significant decrease in later strength. In the prior art, alkaline activators based on sodium hydroxide or sodium silicate are also used. These materials have a high OH content. - can be rapidly released to initiate the hydration reaction of granulated blast furnace slag, but Ca 2+ Since it is not possible to provide high strength hydration products such as ettringite crystals, the strength of this cement system is not high. In the prior art, calcium oxide or calcium hydroxide alkaline activators are also used, but the action mechanism of calcium oxide or calcium hydroxide and granulated blast furnace slag is not fully understood, and the hazards and mechanisms caused by excess calcium oxide or calcium hydroxide cannot be understood, so the amount of such activators is excessive, and no cement with excellent performance is produced.
[0027] Compared with the prior art, the present invention has the following beneficial effects: In the ultra-low carbon clinker-free cement provided by the present invention, quicklime, slaked lime, etc., which are non-clinker components rich in free calcium oxide, are directly added, and the ratio of free calcium oxide in the formulation is controlled within an appropriate range, so that the free calcium oxide and / or calcium hydroxide are contained in an appropriate amount of Ca at the early stage of hydration. 2+ and OH - By rapidly releasing calcium hydroxide and inducing a reaction of granulated blast furnace slag, it can react with gypsum to produce ettringite, which has high strength, small expansion, high carbonation resistance, and corrosion resistance. By controlling the content of free calcium oxide and / or calcium hydroxide, Ca 2+ and OH - This avoids the formation of calcium monosulfoaluminate hydrate, which has low strength, is easily carbonated, and has no corrosion resistance due to the reaction with aluminum gel and ettringite caused by an excess of . The ultra-low carbon clinker-free cement of the present invention has technical advantages such as high early strength, very high later strength, small shrinkage, carbonation resistance, and low carbon dioxide emissions. [Brief description of the drawings]
[0028] [Figure 1] FIG. 2 is a comparative diagram of DTA curves of hydration products obtained when the cement of Example 1 and the cement of Comparative Example 2 were cured for 28 days. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] According to the present invention, there is provided an ultra-low carbon clinker-free cement. The ultra-low carbon clinker-free cement is produced from granulated blast furnace slag, gypsum, and calcium oxide-based raw materials. The weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is controlled to 0.05% to 0.75%. Preferably, the weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is controlled to 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.2%. More preferably, the percentage of the granulated blast furnace slag to the total weight of the raw materials may be 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%. More preferably, the percentage of the gypsum to the total weight of the raw materials may be 4.5%, 5.0%, 8%, 10%, 12.5%, 15%, 18%, 20%, 22.5%, 25%, 27.5%, 30%, 32%, or 34.5%. More preferably, the content of free calcium oxide relative to the total weight of the resulting cement raw materials is 0.05%, 0.08%, 0.1%, 0.12%, 0.16%, 0.18%, 0.25%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7% or 0.75%.
[0030] Another ultra-low carbon clinker-free cement provided by the present invention is produced from granulated blast furnace slag, gypsum, a cement admixture, and calcium oxide-based raw materials. The weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.75%. Preferably, the weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.2%. More preferably, the percentage of the granulated blast furnace slag to the total weight of the raw materials is 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, or 60%. , 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%. More preferably, the percentage of gypsum based on the total raw material weight may be 4.5%, 5.0%, 8%, 10%, 12.5%, 15%, 18%, 20%, 22.5%, 25%, 27.5%, 30%, 32% or 34.5%. More preferably, the percentage of said cement mix relative to the total weight of the raw materials may be 0.65%, 1.5%, 5.5%, 7.5%, 10.5%, 12.5%, 15.5%, 17.5%, 20.5%, 22.5%, 25.5%, 27.5%, 30.5% or 32%. More preferably, the content of free calcium oxide relative to the total weight of the resulting cement raw materials is 0.05%, 0.08%, 0.1%, 0.12%, 0.16%, 0.18%, 0.25%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7% or 0.75%.
[0031] Another ultra-low carbon clinker-free cement provided by the present invention is produced from granulated blast furnace slag, gypsum, a setting control and strength enhancing component, and a calcium oxide-based raw material. The weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.75%. Preferably, the weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.2%. More preferably, the percentage of the granulated blast furnace slag to the total weight of the raw materials may be 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%. More preferably, the percentage of the gypsum to the total weight of the raw materials may be 4.5%, 5.0%, 8%, 10%, 12.5%, 15%, 18%, 20%, 22.5%, 25%, 27.5%, 30%, 32%, or 34.5%. More preferably, the percentage of said set modifier and strength enhancer relative to the total weight of the raw materials may be 0.9%, 1.0%, 1.2%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 1.95%. More preferably, the percentage by weight of free calcium oxide relative to the total weight of the resulting cement raw materials is 0.05%, 0.08%, 0.1%, 0.12%, 0.16%, 0.18%, 0.25%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7% or 0.75%.
[0032] Another ultra-low carbon clinker-free cement provided by the present invention is produced from granulated blast furnace slag, gypsum, cement admixture, setting control and strength enhancing components, and calcium oxide-based raw materials. The weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.75%. Preferably, the weight percentage of free calcium oxide relative to the total weight of the obtained cement raw materials is 0.05% to 0.7%, more preferably 0.05% to 0.6%, more preferably 0.05% to 0.5%, even more preferably 0.10% to 0.5%, and most preferably 0.16% to 0.2%. More preferably, the percentage of the granulated blast furnace slag to the total weight of the raw materials is 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%. , 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%. More preferably, the percentage of gypsum based on the total raw material weight may be 4.5%, 5.0%, 8%, 10%, 12.5%, 15%, 18%, 20%, 22.5%, 25%, 27.5%, 30%, 32% or 34.5%. More preferably, the percentage of the cement mix relative to the total weight of the raw materials may be 0.65%, 1.5%, 5.5%, 7.5%, 10.5%, 12.5%, 15.5%, 17.5%, 20.5%, 22.5%, 25.5%, 27.5%, 30.5% or 32%. More preferably, the percentage of the set modifier and strength enhancer relative to the total weight of the raw materials may be 0.9%, 1.0%, 1.2%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 1.95%.More preferably, the content of free calcium oxide relative to the total weight of the resulting cement raw materials may be 0.05%, 0.08%, 0.1%, 0.12%, 0.16%, 0.18%, 0.25%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7% or 0.75%.
[0033] In the ultra-low carbon clinker-free cement provided by the present invention, the gypsum is any one or a combination of two or more of natural gypsum dihydrate, natural anhydrite, hemihydrate, α-type high-strength gypsum, desulfurized gypsum, phosphate gypsum, and hydrofluoric gypsum. Preferably, the gypsum is any one or a combination of two or more of natural gypsum dihydrate, natural anhydrite, hemihydrate, and desulfurized gypsum.
[0034] In the ultra-low carbon clinker-free cement provided by the present invention, the calcium oxide-based material is a material containing free calcium oxide as a main component and having a free calcium oxide content of 30% to 80%. For example, the free calcium oxide content may be ≧30%, ≧35%, ≧40%, ≧45%, ≧50%, ≧55%, ≧60%, ≧65%, ≧70%, ≧75%, or ≧80%. The free calcium oxide is a general term for components present in the raw material in the form of free calcium oxide and / or calcium hydroxide not bound to acidic oxides. The free calcium oxide content can be measured by the test method specified in the national standard GB / T 176-2017. Preferably, the calcium oxide-based material is any one or a combination of two or more of quicklime, slaked lime, industrial calcium oxide, industrial calcium hydroxide, carbide slag, calcium oxide-based expanding agent, and ettringite-based expanding agent. More preferably, the calcium oxide-based material is any one or a combination of two or more of quicklime, slaked lime, and carbide slag.
[0035] In the above embodiment of the present invention, the cement admixture is any one or a combination of two or more of fly ash, steel slag, limestone, dolomite, pozzolanic admixture or sandstone. The introduction of the cement admixture further reduces the cost and the carbon footprint of the cement described in the present invention.
[0036] In the above embodiment of the present invention, the setting control / strength enhancing component is any one or a combination of two or more selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium sulfate, sodium sulfate, potassium sulfate, aluminum sulfate, lithium carbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium silicate, lithium chloride, citric acid, sodium citrate, or sodium gluconate. Preferably, the setting control / strength enhancing component is any one or a combination of two or more selected from lithium hydroxide, sodium hydroxide, lithium sulfate, sodium sulfate, aluminum sulfate, lithium carbonate, citric acid, sodium citrate, or sodium gluconate.
[0037] Hereinafter, the embodiments and technical effects of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to the following examples.
[0038] Examples 1 to 11 The ultra-low carbon clinker-free cement was produced from raw materials consisting of 78.75% to 79.94% granulated blast furnace slag, 20% natural gypsum, and the remainder quicklime, as shown in Table 1 below. The CaO content in the quicklime was 80%.
[0039] The manufacturing steps are as shown in Table 1 below. After mixing all the raw materials, the mixture is mixed with a 500m2 powder with a specific surface area of 500m2. 2 / kg, then uniformly mix them in a ratio to control the weight percentage of free calcium oxide to 0.05%-1.00%, thereby obtaining ultra-low carbon clinker-free cement.
[0040] [Table 1]
[0041] Examples 12 to 20 The ultra-low carbon clinker-free cement was produced from raw materials containing 65.30% to 95.30% granulated blast furnace slag, 4.50% to 34.50% natural gypsum, and 0.2% quicklime by weight percentage, as shown in Table 2 below. The CaO content in the quicklime was 80%.
[0042] The manufacturing steps are as shown in Table 2 below. After mixing all the raw materials, the mixture is mixed with a 500m2 powder with a specific surface area of 500m2. 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0043] [Table 2]
[0044] Examples 21 to 25 The ultra-low carbon clinker-free cement was produced from raw materials, as shown in Table 3 below, of 79.80% granulated blast furnace slag, 20.00% natural gypsum dihydrate and 0.20% quicklime by weight percentage. The CaO content in the quicklime was 80%.
[0045] The manufacturing process involves mixing all the raw materials and then mixing them into a mixture with a specific surface area of 200 to 1200 m. 2 / kg, and uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16% to obtain ultra-low carbon clinker-free cement.
[0046] [Table 3]
[0047] Examples 26 to 32 The ultra-low carbon clinker-free cement was produced from raw materials containing 79.20% to 79.82% granulated blast furnace slag, 20.00% natural gypsum, and the remainder quicklime or hydrated lime, as shown in Table 4 below. The CaO content in the calcium oxide-based raw materials was 20% to 90%.
[0048] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0049] [Table 4]
[0050] Examples 33 to 41 The ultra-low carbon clinker-free cement was produced from raw materials containing 47.80% to 79.15% granulated blast furnace slag, 20% natural gypsum, 0.65% to 32% fly ash, and 0.20% quicklime by weight percentage, as shown in Table 5 below. The CaO content in the quicklime was 80%.
[0051] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0052] [Table 5]
[0053] Examples 42 to 50 The ultra-low carbon clinker-free cement was produced from raw materials containing 47.80% to 79.15% granulated blast furnace slag, 20% natural gypsum, 0.65% to 32% limestone powder, and 0.20% quicklime, as shown in Table 6 below. The CaO content in the quicklime was 80%.
[0054] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0055] [Table 6]
[0056] Examples 51 to 55 The ultra-low carbon clinker-free cement was produced from raw materials, as shown in Table 7 below, containing 61.80% granulated blast furnace slag, 20% natural gypsum, 2% to 16% fly ash, 2% to 16% limestone powder, and 0.20% quicklime, by weight percentage. The CaO content in the quicklime was 80%.
[0057] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0058] [Table 7]
[0059] Examples 56 to 76 The ultra-low carbon clinker-free cement was produced from raw materials containing 77.85%~79.80% granulated blast furnace slag, 20% natural gypsum, 0.9%~1.95% setting control and strength enhancing components, and 0.20% quicklime, as shown in Table 8 below. The CaO content in the quicklime was 80%.
[0060] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0061] [Table 8]
[0062] Examples 77 to 80 The ultra-low carbon clinker-free cement was produced from raw materials containing 60.60% granulated blast furnace slag, 20% natural gypsum, 18% admixture, 1.2% setting control and strength enhancing components, and 0.20% quicklime, as shown in Table 9. The CaO content in the quicklime was 80%.
[0063] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0064] [Table 9]
[0065] Application example 1-11 The ultra-low carbon clinker-free cements of Examples 1 to 11 and water were prepared into pastes according to Section 7.2 of GB 1346 with a water / binder ratio of 0.4, molded according to Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days according to Section 8 of GB / T 17671, and their compressive strength and flexural strength were measured according to Section 9 of GB / T 17671. The measurement results are shown in Table 10.
[0066] [Table 10]
[0067] As shown in Table 10 above, the ultra-low carbon clinker-free cement of Examples 1-11 of the present invention does not contain Portland cement clinker, and free calcium oxide-rich quicklime is directly added as an activator, and the total calcium oxide contained in the total amount of raw materials is controlled within a specified range (0.05% to 0.75%), so that the final cement has very excellent early and late strength. The cement of the above examples has a compressive strength of 11-27.4 MPa and a flexural strength of 3.3-8.2 MPa after molding and curing for one day, and after three days, the compressive strength reached 40 MPa or more and the flexural strength also reached 10 MPa or more. This is because free calcium oxide that undergoes hydration reaction is directly added via quicklime to produce an appropriate amount of Ca. 2+ and OH - The cement has relatively high initial strength because the granulated blast furnace slag is activated by the rapid release of hydrogen and the rapid reaction with water. The cement of the above example also has a compressive strength of 60-85 MPa and a flexural strength of 12-14 MPa after molding and curing for 28 days, showing very high later strength.
[0068] Application example 12-20 The ultra-low carbon clinker-free cements of Examples 12 to 20 and water were mixed into pastes in a water / binder ratio of 0.4 according to GB 1346, section 7.2, molded according to GB / T 17671, section 7, cured for 1 day, 3 days and 28 days according to GB / T 17671, section 8, and measured for compressive strength and flexural strength according to GB / T 17671, section 9. The results are shown in Table 11.
[0069] [Table 11]
[0070] As shown in Table 11 above, the gypsum in the ultra-low carbon clinker-free cement of Examples 12-20 of the present invention is 4.5%-34.5% of the total weight of the raw materials, and the strength at 1 day, 3 days and 28 days tends to increase first and then decrease with the increase in the gypsum content, and it is most preferable that the gypsum content is in the range of 15%-20%. Within this range, it has high early strength and very high later strength. This shows that if the gypsum content in the raw materials is controlled within an appropriate range, the cement can have ideal early and later strength.
[0071] Application Examples 21-25 The ultra-low carbon clinker-free cements of Examples 21 to 25 and water were mixed into pastes in a water / binder ratio of 0.4 according to GB 1346, section 7.2, molded according to GB / T 17671, section 7, cured for 1 day, 3 days and 28 days according to GB / T 17671, section 8, and measured for compressive strength and flexural strength according to GB / T 17671, section 9. The results are shown in Table 12.
[0072] [Table 12]
[0073] As shown in Table 12 above, the ultra-low carbon clinker-free cements of Examples 21-25 of the present invention have similarly high early strength and very high later strength. This indicates that if the content of free calcium oxide in the raw materials is controlled within an appropriate range, the cement can have ideal early and later strength. The grinding degree of the raw materials also has a certain influence on the cement performance. By improving the grinding degree of the raw materials, the activity of the raw materials is improved, the hydration reaction rate is increased, and the early strength of the cement is significantly improved, but if the raw materials are ground too much, the early reaction rate is too fast, so the later strength may be slightly reduced.
[0074] Application Example 26-32 The ultra-low carbon clinker-free cements of Examples 26 to 32 and water were mixed into pastes in a water / binder ratio of 0.4 according to GB 1346, section 7.2, molded according to GB / T 17671, section 7, cured for 1 day, 3 days and 28 days according to GB / T 17671, section 8, and measured for compressive strength and flexural strength according to GB / T 17671, section 9. The results are shown in Table 13.
[0075] [Table 13]
[0076] As shown in Table 13 above, the ultra-low carbon clinker-free cement of Examples 26-32 of the present invention has high early strength and very high later strength. If the content of free calcium oxide in the raw material is controlled within an appropriate range, the cement can have ideal early and later strength. The purity and type of calcium oxide-based raw material may be different according to the actual situation.
[0077] Application Examples 33-41 The ultra-low carbon clinker-free cements of Examples 33 to 41 and water were mixed into pastes in a water / binder ratio of 0.4 according to GB 1346, section 7.2, molded according to GB / T 17671, section 7, cured for 1 day, 3 days and 28 days according to GB / T 17671, section 8, and measured for compressive strength and flexural strength according to GB / T 17671, section 9. The results are shown in Table 14.
[0078] [Table 14]
[0079] Application Examples 42-49 The ultra-low carbon clinker-free cements of Examples 42 to 49 and water were mixed into pastes in a water / binder ratio of 0.4 according to GB 1346, section 7.2, molded according to GB / T 17671, section 7, cured for 1 day, 3 days and 28 days according to GB / T 17671, section 8, and measured for compressive strength and flexural strength according to GB / T 17671, section 9. The results are shown in Table 15.
[0080] [Table 15]
[0081] Application Examples 51-55 The ultra-low carbon clinker-free cements of Examples 51 to 55 and water were mixed into pastes in a water / binder ratio of 0.4 according to GB 1346, section 7.2, molded according to GB / T 17671, section 7, cured for 1 day, 3 days and 28 days according to GB / T 17671, section 8, and measured for compressive strength and flexural strength according to GB / T 17671, section 9. The results are shown in Table 16.
[0082] [Table 16]
[0083] As shown in Tables 13-16 above, the ultra-low carbon clinker-free cements of Examples 26-54 of the present invention have similarly high early strength and very high later strength. If the content of free calcium oxide in the raw materials is controlled within an appropriate range, the cement can have ideal early and later strength. The carbon dioxide emissions of the cements described in the present invention can also be further reduced by adding a certain amount of cement admixture to the raw materials.
[0084] Application Examples 56-76 The ultra-low carbon clinker-free cements of Examples 56 to 76 and water were prepared into pastes according to Section 7.2 of GB 1346 with a water / binder ratio of 0.4, molded according to Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days according to Section 8 of GB / T 17671, and their compressive strength and flexural strength were measured according to Section 9 of GB / T 17671. The measurement results are shown in Table 17.
[0085] [Table 17]
[0086] Application Examples 77-80 The ultra-low carbon clinker-free cements of Examples 77 to 80 and water were prepared into pastes according to Section 7.2 of GB 1346 with a water / binder ratio of 0.4, molded according to Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days according to Section 8 of GB / T 17671, and their compressive strength and flexural strength were measured according to Section 9 of GB / T 17671. The measurement results are shown in Table 18.
[0087] [Table 18]
[0088] As shown in Tables 17-18 above, the ultra-low carbon clinker-free cements of Examples 56-80 of the present invention have similarly high early strength and very high later strength. If the content of free calcium oxide in the raw materials is controlled within an appropriate range, the cement can have ideal early and later strength. The carbon dioxide emission of the cement described in the present invention can be further reduced by adding a specific amount of cement admixture to the raw materials, and the early strength of the cement can be further improved by adding a specific amount of setting control and strength enhancing components to the raw materials.
[0089] In the process of proposing the present invention, the inventors obtained an ideal ultra-low carbon clinker-free cement through the experiments in the above examples, and also demonstrated through larger-scale experiments that the performance of the cement would be reduced if the raw materials were used in a different blend ratio. Only representative comparative examples will be selected and explained below.
[0090] Comparative Example 1 The ultra-low carbon clinker-free cement was produced using raw materials containing 80% granulated blast furnace slag and 20% natural gypsum by weight, as shown in Table 19 below. The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg and then uniformly mixed in proportion to obtain ultra-low carbon clinker-free cement.
[0091] [Table 19]
[0092] Comparative Example 2 The ultra-low carbon clinker-free cement was produced from raw materials containing 77.50% granulated blast furnace slag, 20% natural gypsum, and 2.5% quicklime by weight percentage, as shown in Table 20 below. The CaO content in the quicklime was 80%.
[0093] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 2%, thereby obtaining ultra-low carbon clinker-free cement.
[0094] [Table 20]
[0095] Comparative Example 3 The ultra-low carbon clinker-free cement was produced from raw materials containing 59.80% granulated blast furnace slag, 40% natural gypsum, and 0.2% quicklime by weight percentage, as shown in Table 21 below. The CaO content in the quicklime was 80%.
[0096] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0097] [Table 21]
[0098] Comparative Example 4 The ultra-low carbon clinker-free cement was produced from raw materials containing 96.80% granulated blast furnace slag, 3% natural gypsum, and 0.2% quicklime by weight as shown in Table 22 below. The CaO content in the quicklime was 80%.
[0099] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0100] [Table 22]
[0101] Comparative Example 5 The ultra-low carbon clinker-free cement was produced from raw materials containing 79.80% granulated blast furnace slag, 20% natural gypsum, and 0.2% quicklime by weight percentage, as shown in Table 23 below. The CaO content in the quicklime was 80%.
[0102] The manufacturing process involves mixing all the raw materials and then mixing them into a mixture with a specific surface area of 100 m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0103] [Table 23]
[0104] Comparative Example 6 The ultra-low carbon clinker-free cement was produced from raw materials containing 79.80% granulated blast furnace slag, 20% natural gypsum, and 0.2% quicklime by weight percentage, as shown in Table 24 below. The CaO content in the quicklime was 80%.
[0105] The manufacturing process involves mixing all the raw materials and then mixing them into a mixture with a specific surface area of 1400 m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0106] [Table 24]
[0107] Comparative Example 7 The ultra-low carbon clinker-free cement was produced from raw materials containing 39.80% granulated blast furnace slag, 20% natural gypsum, 40% fly ash, and 0.2% quicklime by weight percentage, as shown in Table 25 below. The CaO content in the quicklime was 80%.
[0108] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0109] [Table 25]
[0110] Comparative Example 8 The ultra-low carbon clinker-free cement was produced from raw materials containing 76.80% granulated blast furnace slag, 20% natural gypsum, 3% sodium hydroxide, and 0.2% quicklime by weight percentage, as shown in Table 26 below. The CaO content in the quicklime was 80%.
[0111] The manufacturing process involves mixing all the raw materials together and then mixing them into a mixture with a specific surface area of 500m 2 / kg, then uniformly mixed in proportion to control the weight percentage of free calcium oxide to 0.16%, to obtain ultra-low carbon clinker-free cement.
[0112] [Table 26]
[0113] Comparative application example 1 The ultra-low carbon clinker-free cement of Comparative Example 1 and water were used to prepare a paste in accordance with Section 7.2 of GB 1346 with a water / binder ratio of 0.4, which was then molded in accordance with Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days in accordance with Section 8 of GB / T 17671, and its compressive strength and flexural strength were measured in accordance with Section 9 of GB / T 17671. The measurement results are shown in Table 27.
[0114] [Table 27]
[0115] In the ultra-low carbon clinker-free cement of this comparative example, the raw material did not contain a calcium oxide-based alkaline activator, so the granulated blast furnace slag was not activated, and the cement had almost no strength in the early stages and extremely low strength in the later stages.
[0116] Comparative application example 2 The ultra-low carbon clinker-free cement of Comparative Example 2 and water were used to prepare a paste according to Section 7.2 of GB 1346 with a water / binder ratio of 0.4, which was then molded according to Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days according to Section 8 of GB / T 17671, and its compressive strength and flexural strength were measured according to Section 9 of GB / T 17671. The measurement results are shown in Table 28.
[0117] [Table 28]
[0118] The ultra-low carbon clinker-free cement used in this comparative example was the ultra-low carbon clinker-free cement of Comparative Example 2, and because excessive quicklime was added to the raw material, there was too much calcium oxide involved in the hydration reaction. The excess calcium oxide caused the alkalinity of the pore solution to become too high, inhibiting the formation of ettringite, reducing the amount of ettringite formed in the system and decreasing the strength. (The inventors compared the DTA curves of the hydration products of two types of cement stones, Application Example 1 of the present invention and Application Example 2, which were cured for 28 days, and found that the peak of ettringite in this comparative example was clearly lower than the peak of ettringite in Application Example 1. This shows that the amount of ettringite formed in this comparative example was clearly less than that in Application Example 1. A comparison of the DTA curves of the hydration products is shown in Figure 1.) On the other hand, the excess free calcium oxide reacts with aluminum gel and ettringite to form calcium monosulfoaluminate hydrate, which has low strength, is easily carbonated, and has no corrosion resistance. This reaction reduces the volume of the product, loosens the hardened body, and increases the porosity. This reaction also consumes the aluminum gel that acts as a gel, and the amount of gel in the system is not enough to bond with other substances, so the strength of the cement is significantly reduced, and the generated calcium monosulfoaluminate hydrate is easily carbonated, which makes the cement prone to corrosion. The final cement was significantly improved compared to the cement of Comparative Example 1, but both the early strength and later strength were poor compared to the cements of the respective application examples of the present invention.
[0119] Comparative application example 3 The ultra-low carbon clinker-free cement of Comparative Example 3 and water were used to prepare a paste according to Section 7.2 of GB 1346 with a 0.4 water-binder ratio, molded according to Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days according to Section 8 of GB / T 17671, and measured its compressive strength and flexural strength according to Section 9 of GB / T 17671. The measurement results are shown in Table 29.
[0120] [Table 29]
[0121] In this comparative application example, the amount of granulated blast furnace slag added in the ultra-low carbon clinker-free cement was too low, and the amount of gypsum added was too high, so that gypsum remained in the system and the system loosened and even cracked due to the large size of the rod-shaped crystals, and therefore the obtained cement had neither ideal early strength nor later strength.
[0122] Comparative application example 4 The ultra-low carbon clinker-free cement of Comparative Example 4 and water were used to prepare a paste in accordance with Section 7.2 of GB 1346 with a water / binder ratio of 0.4, which was then molded in accordance with Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days in accordance with Section 8 of GB / T 17671, and its compressive strength and flexural strength were measured in accordance with Section 9 of GB / T 17671. The measurement results are shown in Table 30.
[0123] [Table 30]
[0124] In this comparative application example, the amount of granulated blast furnace slag added in the ultra-low carbon clinker-free cement was too high, and the amount of gypsum-based raw material added was too low, which reduced the amount of reactants necessary for the production of ettringite and reduced the amount of ettringite, the main hydration product, produced. As a result, both the early strength and later strength of the obtained cement were not ideal.
[0125] Comparative application example 5 The ultra-low carbon clinker-free cement of Comparative Example 5 and water were prepared into a paste according to Section 7.2 of GB 1346 with a water-binder ratio of 0.4, molded according to Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days according to Section 8 of GB / T 17671, and its compressive strength and flexural strength were measured according to Section 9 of GB / T 17671. The measurement results are shown in Table 31.
[0126] [Table 31]
[0127] In this comparative application example, the ultra-low carbon clinker-free cement raw material was not sufficiently ground, making it difficult for the gypsum and quicklime to quickly destroy the slag glass, and the slag was difficult to activate, so the initial strength and later strength of the resulting cement were not ideal.
[0128] Comparative application example 6 The ultra-low carbon clinker-free cement of Comparative Example 6 and water were used to prepare a paste in accordance with Section 7.2 of GB 1346 with a water / binder ratio of 0.4, which was then molded in accordance with Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days in accordance with Section 8 of GB / T 17671, and its compressive strength and flexural strength were measured in accordance with Section 9 of GB / T 17671. The measurement results are shown in Table 32.
[0129] [Table 32]
[0130] In this comparative application example, the ultra-low carbon clinker-free cement raw material was crushed too much, which not only resulted in high processing costs, but also in the rapid generation of hydration products such as ettringite, which increased the pores inside the cement stone and made it less dense, resulting in neither ideal initial nor later strength of the resulting cement.
[0131] Comparative application example 7 The ultra-low carbon clinker-free cement of Comparative Example 7 and water were used to prepare a paste in accordance with Section 7.2 of GB 1346 with a water / binder ratio of 0.4, which was then molded in accordance with Section 7 of GB / T 17671, cured for 1 day, 3 days and 28 days in accordance with Section 8 of GB / T 17671, and its compressive strength and flexural strength were measured in accordance with Section 9 of GB / T 17671. The measurement results are shown in Table 33.
[0132] [Table 33]
[0133] In this comparative application example, the amount of fly ash, which has a relatively low activity, added to the raw materials for the ultra-low carbon clinker-free cement was too high, and the content of slag, which has a relatively high activity, was relatively low, so that the initial strength and later strength of the obtained cement were not ideal.
[0134] Comparative Application Example 8 The ultra-low carbon clinker-free cement of Comparative Example 8 and water were mixed into pastes in a water / binder ratio of 0.4 according to GB 1346, section 7.2, molded according to GB / T 17671, section 7, cured for 1 day, 3 days and 28 days according to GB / T 17671, section 8, and measured for compressive strength and flexural strength according to GB / T 17671, section 9. The measurement results are shown in Table 34.
[0135] [Table 34]
[0136] In this comparative application example, the amount of sodium hydroxide added, which is a setting adjustment and strength enhancing component in the raw materials of the ultra-low carbon clinker-free cement, was too high, which not only increased the production costs but also made the system too alkaline due to the excess sodium hydroxide, inhibiting the formation of the main hydration product, ettringite, so that the initial and later strengths of the obtained cement were not ideal.
Claims
[Claim 1] An ultra-low carbon clinker-free cement, The calcium oxide-based raw material is composed of 79.47% to 79.82% granulated blast furnace slag, 20% gypsum, and a free calcium oxide content of 30 to 80% by weight. The weight percentage of the free calcium oxide relative to the total weight of the raw materials is 0.16%. The specific surface area of the raw material is 500 m. 2 / kg, The free calcium oxide is a component that is present in the raw materials in the form of free calcium oxide and / or calcium hydroxide that is not bound to acidic oxides in the raw materials.
Citation Information
Patent Citations
Environmental-friendly clinker-free cement and preparation method thereof
CN101525217A
Environment-protection type clinker-free cement and its preparation method
CN1405108A
Hydraulic cement composition
JP2010285301A
Concrete binder for blast furnace cement concrete
JP2016023105A
Hydraulic composition
JP2016056083A